British Association for Irish Studies Executive elections 1992. Guidance on ballot - British Association for Irish Studies, BAIS (1992)
BAIS (British Association for Irish Studies) Executive elections 1992 typescript guidance on ballot. Deadline stated as 14 October 1990.